C286, an orally available retinoic acid receptor β agonist drug, regulates multiple pathways to achieve spinal cord injury repair - Goncalves, Maria B.; Wu, Yue; Clarke, Earl; Grist, John; Moehlin, Julien; Mendoza-Parra, Marco Antonio; Hobbs, Carl; Kalindjian, Barret; Fok, Henry; Mander, Adrian P.; Hassanin, Hana; Bendel, Daryl; et al. (Frontiers in Molecular Neuroscience, 2024)
Retinoic acid receptor β2 (RARβ2) is an emerging therapeutic target for spinal cord injuries (SCIs) with a unique multimodal regenerative effect. We have developed a first-in-class RARβ agonist drug, C286, that modulates neuron-glial pathways to induce functional recovery in a rodent model of sensory root avulsion. Here, using genome-wide and pathway enrichment analysis of avulsed rats' spinal cords, we show that C286 also influences the extracellular milieu (ECM). Protein expression studies showed that C286 upregulates tenascin-C, integrin-α9, and osteopontin in the injured cord. Similarly, C286 remodulates these ECM molecules, hampers inflammation and prevents tissue loss in a rodent model of spinal cord contusion C286. We further demonstrate C286's efficacy in human iPSC-derived neurons, with treatment resulting in a significant increase in neurite outgrowth. Additionally, we identify a putative efficacy biomarker, S100B, which plasma levels correlated with axonal regeneration in nerve-injured rats. We also found that other clinically available retinoids, that are not RARβ specific agonists, did not lead to functional recovery in avulsed rats, demonstrating the requirement for RARβ specific pathways in regeneration. In a Phase 1 trial, the single ascending dose (SAD) cohorts showed increases in expression of RARβ2 in white blood cells correlative to increased doses and at the highest dose administered, the pharmacokinetics were similar to the rat proof of concept (POC) studies. Collectively, our data suggests that C286 signalling in neurite/axonal outgrowth is conserved between species and across nerve injuries. This warrants further clinical testing of C286 to ascertain POC in a broad spectrum of neurodegenerative conditions.